Readings in business cycle theory - American economic association (Great Britain : Bradford and Dickens, 1950)
Readings in business cycle theory aims at the tuition of senior and graduate university students of economics. The book is divided into 6 parts: overall picture of the business cycle and method analysis; savings, investment and national income; the multiplier, acceleration principle and government spending; monetary theory of the business cycle; under-consumption theory and secular stagnation thesis; and special commodity cycles.
Bibliographical foot-notes. "Classified bibliography of articles on business cycle theory, compiled by Harold M. Somers": p. 443-487.
lje 18/10/18
Loans
Keywords: Business cycles; Economic growth